Colton 911: in hot pursuit - Krotow, Geri (Colton 911: Grand Rapids., 2020)
"Sergeant Flynn Cruz-Street's estranged half brother is a threat to society. To catch him, Flynn must join forces with JAG paralegal Vikki Colton. Vikki proves to be a brilliant investigator, and what starts as a reluctant partnership soon blossoms into an irresistible attraction. But as they work tirelessly to track down the dangerous criminal, Flynn and Vikki must resist the sparks between them...or risk losing their very lives" --Amazon.